Identificación de inmunoglobulinas para la determinación de fiebre aftosa en camélidos sudamericanos (alpacas) - Aguaiza Aguaiza, Oscar Vinicio (2017)
The present investigation had relevance at the determination of immunoglobulins that intervene in foot - and - mouth disease in South American camelids (alpacas). For this purpose, the identification of twelve experimental units available at the Faculty of Agricultural Sciences and Natural Resources of the Technical University of Cotopaxi, were used for the application of the foot-and-mouth disease vaccine under study. At the execution of the work a direct observation was made, evaluating the following parameters such as: body condition, health, revision of records. The first sampling was done by the technique of vein puncture in the femoral vein. The amount of blood that was extracted was of 5ml to 10ml in vacutainer tubes of red cap, making the respective identification and after sent to the laboratory for the analysis of the sanguine serum. Sampling was performed twice, with the following results: IgA in the first trial showed a value of 14.1 mg / dl; After inoculation of the foot-and-mouth disease strain at 15 days, expressed 26.5 mg / dl results. For the IgG it showed an amount of 1621.2 mg / dl and once inoculated, the effect was 1629 mg / dl. For the IgM presented values of 27.8 mg / dl, post inoculation were 97.9 mg / dl; Demonstrating that there is an increase of 12.4% for IgA, 7.8% for IgG and 71.1 for IgM, indicating that the animal developed a positive immune response.